A articulação entre assistentes sociais e sujeitos coletivos de Sorocaba: uma análise sobre o período crítico da pandemia de COVID-19 - Souza, Daniel Nogueira de (2023)
This dissertation aims to analyze how the articulations carried out by social workers and collective subjects in the municipality of Sorocaba took place during the years 2020 and 2021 - called the “critical period of the covid-19 pandemic” in the light of verifying whether these relationships enabled rapprochement and involvement between these two groups. Based on the application of two electronic questionnaires, we sought to understand how Sorocaba professionals devised strategies to face the challenging period of the Covid-19 pandemic, in its dimensions of risk of being affected by the virus, but also under the situation of worsening health in a world of precarious work; just as we also seek to understand how activists of collective subjects dealt with the pandemic from the aspect of organizing solutions and responses in the political and practical dimension of collective actions, especially in light to verify the incidence of specificities of the new organizational formats that constitute the movements on the scene in the country's recent history as organizations different from the traditional ones within the arena of disputes. It is important to consider that the way of reacting and contesting the critical situation of the pandemic emphasizes aspects already recognized by the bibliography on the subject regarding the participants in our research, namely: the institutional limits of social workers, ICTs as mediators of wear and tear around work increasingly intensified and precarious, the profession's vigilance in relation to not distancing itself from the fundamental critical bases of social work in terms of conservatism and fundamentalism; as well as society organized within today's parameters format ways of organizing alternative to the traditional hierarchies of social movements, emphasizing that the relationship with the virtual world and the real world is inseparable from everyday political practice, which, mediated by ICTs, has its capacity expanded